The Use of Noble Gases to Constrain Subsurface Fluid Dynamics in the Hydrocarbon Systems - Li, Yan; Cao, Chunhui; Hu, Hongyu; Huang, Huanfang (Frontiers in Earth Science, 2022)
Geochemical techniques have been widely applied to study the generation and migration of hydrocarbons in sedimentary basins over the last several decades. Diagnostic biomarkers and stable carbon and hydrogen isotopes (such as δ13C and D) are generally used to identify the sources and thermal maturity of hydrocarbons, to reveal the accumulation process and mechanism of oil and gas reservoirs. However, some questions, such as secondary migration processes and pathways of oil and gas, and the relationship between groundwater flow and hydrocarbon transport, remain unclear and challenging. The low abundance and chemical inertness properties allow noble gases to serve as robust tools for tracing subsurface fluid flow. Additionally, they can be used for identifying and quantifying the role of the concomitant groundwater related to the generation and migration of hydrocarbons. This paper reviews the previous modeling work on using noble gases to study the fluid flow, flow paths, and gas/oil-water interactions in hydrocarbon systems. Noble gases from various sources can be readily identified due to their distinct isotopic and elemental signatures. Atmosphere-derived noble gases can be used to evaluate the amount of involved aquifer water associated with the hydrocarbon system and determine the groundwater migration paths and flow rates. Radiogenic noble gases accumulate over time, providing information about the subsurface fluid residence time. Questions concerning the specific trapping sites and mechanisms that affect heavy noble gas adsorption into organic sediments are still unresolved. Investigating the hydrocarbon generation, migration, and subsurface crustal fluid interactions in the hydrocarbon reservoirs can improve our understanding of noble gases as useful tracers in the subsurface environment and provide valuable geological evidence for the exploration and production of petroleum sources.